Inovasi Guru PAI Dalam Mengembangkan Media Pembelajaran Agama Islam di SDN 2 Varia Agung - Juwita Pradina Aprillia; Syaifur Rohman (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to describe the innovations of Islamic Education (PAI) teachers in developing learning media at SDN 2 Varia Agung. The background of this study is that conventional PAI learning methods are still being used, which are less attractive to students and do not encourage their participation. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that PAI teachers at SDN 2 Varia Agung have developed various innovative learning media, such as interactive videos, Islamic applications, digital quizzes, character cards, worship posters, and educational games. These innovations have been proven to increase students' motivation to learn, their understanding of the material, and their religious values. Supporting factors for innovation include school support, student enthusiasm for learning, and the availability of basic learning facilities. The obstacles encountered were limited technological resources and teachers' ability to operate digital media. In conclusion, the learning media innovations implemented by PAI teachers at SDN 2 Varia Agung had a positive impact on the effectiveness of learning and the development of students' religious character.